System approach use for the methodology creation of technical training improvement among qualified boxers - Kolesnik, I. S.; Gatin, F. A.; Osipov, D. A. (The Russian Journal of Physical Education and Sport, 2017)
Striking actions form the main content of qualified boxers` competitive activity. Their effectiveness is conditioned by several factors: the level of general and special physical readiness; the ability to master, analyze and use new information about the means and methods of technical readiness increase among qualified boxers; the influence of technical readiness indices on the tactics of the fight; the use of single and series of striking actions; the ability to control the opponent`s actions; psycho-emotional state control as structural components and technical training components. Material. The article is about the necessity to use system approach in order to reveal structural content of technical readiness; systematize its components and elements. It helps to determine the role and place of each element and component of technical training for boxers` sportsmanship improvement, for the tactics of the fight selection. Research methods: scientific and methodical literature analysis and systematization, progressive pedagogical experience of the specialists-boxing trainers summarizing, pedagogical experiment, testing, mathematical statistics methods. Results. With the level of general and special physical readiness increase the importance of independent training among qualified boxers increases, directed at coordination training indices increase, which is closely connected with the results of competitive activity. Technical training is directed not only at the most effective means and methods of the attacking and defensive techniques use, but also at the following important components formation: motivation and goal-setting, motor memory, attention, perception development, objective estimation of own activity and also spatio-temporal and spatio-power parameters of the opponent`s motor acts. Conclusion. The results of the pedagogical experiment proved the effectiveness of technical training improvement methodology among qualified boxers, created on the basis of system analysis according to the degree of motivation and goal-setting formation, motor memory improvement, the opponent`s and own actions estimation and analysis.